Mapping the Whole School Approach in social and emotional learning and wellbeing: a bibliometric review with implications for social work and education - Cădariu, Ioana-Eva; Rad, Dana (Technium Social Sciences Journal, 2025)
The focus of this study is to conduct bibliometric research of relevant publications on the whole school approach (WSA) in relation to social and emotional learning (SEL) and wellbeing from the Web of Science Core Collection until May 2025. An analysis of 503 publications was undertaken with VOSviewer to discover patterns of co-occurrence, conceptual clusters, and citation networks. Four dominant thematic areas emerged: systemic implementation and school ecology; health promotion and psychosocial wellbeing; behavioral risk prevention and student connectedness; and teacher competence, policy, and inclusion. Data indicates a trend towards behaviorist and preventive models to more inclusive holistic frameworks that center on resilience, participation, transformation, and relational aspects of systems. There is still an overwhelming concentration of research from high-income countries, with a stark absence of the Global South, and under-explored integration of practitioner and student perspectives, despite increasing global adoption. By identifying these gaps, this study aims to assist literature by mapping contemporary trends, gaps in policy and practice and forecast strategies for the future. It calls for integration of whole school approaches that is multi-level, culturally attuned, participatory, digitally focused, and aligned with the Sustainable Development Goals.